Studi Literatur: Pemilihan Media Pembelajaran Matematika untuk Siswa Sekolah Menengah Atas - Cahyani, Adinda (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
One of the factors that determine the success of learning mathematics is the learning media used. Learning media can help students to make abstract math understandable to students. In addition to media, meaningful learning is learning that is tailored to the cognitive development of students. The research method used in this research is Systematic Literature Review (SLR). Data collection was carried out by documenting and reviewing all articles related to mathematics education from 2010 to 2020. A total of 20 accredited national and international journal articles were used in this study, which were obtained from Google Scholar, Research Gate, SINTA, Scopus, and Taylor & Francis. Based on this research, it was found that learning media can help students to make abstract mathematics more concrete. In addition, meaningful learning is learning that is tailored to students' cognitive development. The use of learning media in accordance with the cognitive level of high school students is one of the alternatives to learning mathematics, such as the use of interactive multimedia, edpuzzle interactive media, and the use of geogebra learning media to help abstract concepts become concrete so that they are understood by students. It is expected that teachers in delivering material by utilizing and using learning media to improve student learning outcomes in learning